Development of an image enhancement method for android applications - Khalifa, Othman Omran; Mohd Halid, Nurul Hazirah; Abdul Malik, Noreha (2020)
Digital image processing plays a vital role in enhancing images as it is said that a picture is worth a thousand words. Image enhancement is the process of improving digital image quality. There are tremendous growths in the techniques used to enhance images due to the advances in technology. Client in today’s world uses various tools for different image processing features while operating in the same digital image. In this paper, an enhancement image method is proposed and implemented as an android application. Few techniques of image enhancement are being applied in the code construction together with another additional features to relocate image position. To test the effectiveness of this application, PSNR comparison test between original and enhanced image and Application user-survey have been conducted.